Standard vs. Modified Antiplatelet Therapy Based on Thromboelastography With Platelet Mapping for Preventing Bleeding Events in Patients Undergoing Stent-Assisted Coil for a Ruptured Intracranial Aneurysm - Li, Yuanshu; Zhang, Xiaodong; Guo, Zongduo; Zhu, Ji; Xu, Rui; He, Zhaohui; Sun, Xiaochuan (Frontiers in Neurology, 2021)
Background and purpose: Stent-assisted coiling (SAC) of intracranial aneurysms is usually treated with antiplatelet therapy to reduce the risk of postoperative ischemic events. However, using the same antiplatelet therapy for all patients may increase the risk of bleeding in patients with aneurysmal subarachnoid hemorrhage (aSAH). Thromboelastography-platelet mapping (TEG-PM) measures platelet function, which reflects the effect of antiplatelet drugs. This study aimed to evaluate the benefits of individualized antiplatelet regimens based on Methods: We retrospectively included patients with aSAH who treated with SAC during the period from June 2012 to December 2019. Patients were divided into 2 groups: patients whose antiplatelet therapy adjusted by TEG-PM parameters after surgery (adjustment group) and patients who treated with standard dual antiplatelet therapy without TEG-PM test (control group). The occurrence of major/minor bleeding events, major/minor thromboembolic events, and favorable outcome (modified Rankin scale < 3) were compared in both groups during hospitalization. Results: Of 187 aSAH patients considered for this study, 145 met the criteria for inclusion and were included in the analysis (93 patients in the adjustment group and 52 patients in the control group). The risks of minor bleeding events (1.1% vs 9.6%, p = 0.02) were significantly lower in patients in the adjustment group. But there was no significant difference in the rate of major bleeding events at discharge between adjustment and control groups (p = 0.35). The rates of thromboembolic events and favorable outcome were similar in both groups (22.6% vs 28.8%, p = 0.42, 95.7% vs 96.2%, p = 1.00 ). Furthermore, the minor thromboembolic events rate was significantly lower in the patients treated with treatment plan C (P=0.02 for treatment plan C versus treatment A, P= 0.03 for treatment plan C versus treatment plan B). But there was no significant difference in the rate of other mentioned above complications and favorable outcomes among patients treated with different antiplatelet regimens. Conclusions: Individualized antiplatelet therapy based on TEG-PM parameters might positively impact the bleeding risk of aSAH patients, without increasing the risk for clinically relevant thromboembolic events.